2011
DOI: 10.1016/j.bbagrm.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin protein ligase, E6-associated protein (E6-AP) regulates PI3K-Akt signaling and prostate cell growth

Abstract: This study elucidates the role of E6-associated protein, E6-AP (a dual function steroid hormone receptor coactivator and ubiquitin-protein ligase) in the regulation of PI3K-Akt signaling pathway, prostate gland growth and proliferation. Here, we report the generation of transgenic mice and prostate cancer cell line, LNCaP cells that overexpress E6-AP protein. Using these models we show that the levels of total Akt and phosphorylated Akt (active Akt) are increased in E6-AP overexpressing prostate gland and LNCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…E6AP is an E3-ligase that regulates the transcript and protein levels of the steroid hormone receptors (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…E6AP is an E3-ligase that regulates the transcript and protein levels of the steroid hormone receptors (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of prostate cancer patients are treated with androgen depletion strategies due to androgen‐dependent progression of prostate cancer, many patients have a relapse with androgen‐independent prostate cancer or exhibit chemoresistance (Feldman & Feldman, ). One reason for development of androgen‐independent prostate cancer therapies is to avoid excessive activation of AKT proteins through mutations of phosphatase and tensin homolog (PTEN) and/or hyper‐activation of PI3K (Kumar et al, ; Srinivasan & Nawaz, ). Therefore, inhibiting the PI3K/AKT signal transduction pathway is an important therapeutic approach for treatment of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that UBE3A can promote proliferation and inhibit apoptosis of cervical cancer cells (4). In prostate cancer cells, UBE3A has been shown to regulate the phosphoinositide 3-kinase-Akt pathway, which results in increased prostate cell growth, proliferation and decreased apoptosis (24). Therefore, it was hypothesized that in breast cancer cells, UBE3A may affect cell signaling pathways and influence cell biological behavior.…”
Section: Discussionmentioning
confidence: 99%